Activated T Lymphocytes are Essential Drivers of Pathological Remodeling in Ischemic Heart Failure. (March 2017) - Bansal, Shyam S.; Ismahil, Mohamed Ameen; Goel, Mehak; Patel, Bindiya; Hamid, Tariq; Rokosh, Gregg; Prabhu, Sumanth D.
Abstract : Background—: Inappropriately sustained inflammation is a hallmark of chronic ischemic heart failure (HF); however, the pathophysiological role of T lymphocytes is unclear. Methods and Results—: Permanent coronary ligation was performed in adult C57BL/6 mice. When compared with sham-operated mice, mice with HF (8 weeks after ligation) exhibited the following features: (1) significant ( P <0.05) expansion of circulating CD3 + CD8 + cytotoxic and CD3 + CD4 + helper (Th) T lymphocytes, together with increased Th1, Th2, Th17, and regulatory T-cell (Treg) CD4 + subsets; (2) significant expansion of CD8 + and CD4 + T cells in failing myocardium, with increased Th1, Th2, Th17, and Treg CD4 + subsets, marked reduction of the Th1/Th2 ratio, augmentation of the Th17/Treg ratio, and upregulation of Th2 cytokines; and (3) significantly increased Th1, Th2, Th17 cells, and Tregs, in the spleen and mediastinal lymph nodes, with expansion of splenic antigen-experienced effector and memory CD4 + T cells. Antibody-mediated CD4 + T-cell depletion in HF mice (starting 4 weeks after ligation) reduced cardiac infiltration of CD4 + T cells and prevented progressive left ventricular dilatation and hypertrophy, whereas adoptive transfer of splenic CD4 + T cells (and, to a lesser extent, cardiac CD3 + T cells) from donor mice with HF induced long-term left ventricular dysfunction, fibrosis, and hypertrophy in naive recipient mice. Conclusions—: CD4 + T lymphocytes are globally expanded and activated in chronic ischemic HF, with Th2 (versus Th1) and Th17 (versus Treg) predominance in failing hearts, and with expansion of memory T cells in the spleen. Cardiac and splenic T cells in HF are primed to induce cardiac injury and remodeling, and retain this memory on adoptive transfer. Abstract : Supplemental Digital Content is available in the text.